دور المنظمات الشعبية والجمعيات الأهلية الشبابية السورية في تعزيز مفاهيم المواطنة الاقتصادية (دراسة ميدانية على الشباب المستفيدين من أنشطة كل منها) - زيود, زينب; دنورة, فاتن حمام علي (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف البحث الحالي إلى تعرف دور المنظمات الشعبية والجمعيات الأهلية العاملة في ميدان الشباب في سورية في تعزيز مفاهيم المواطنة الاقتصادية المتمثلة بـ (حق العمل, وحماية حقوق المستهلك والمنتج, وترشيد استهلاك مصادر الطاقة, والحفاظ على المرافق والممتلكات العامة وغيرها), لدى الشباب المستفيدين من أنشطتها, ولتحقيق أهداف البحث تمّ تصميم استبانة وتوزيعها على عينة مؤلفة من /187/ مستفيد من أنشطة المنظمات الشعبية والجمعيات الأهلية الشبابية السورية, وتوزعت بين /96/ مستفيد من الذكور, و/91/ مستفيد من الإناث, تم سحبها باستخدام العينة الطبقية العشوائية واعتماداً على قانون العينة الإحصائية, وبعد الدراسة والتحليل تمّ التوصل إلى النتائج الآتية: - عدم وجود فروق ذات دلالة إحصائية بين متوسطات استجابات الشباب المستفيدين من أنشطة المنظمات الشعبية، المتصلة بدور تلك المنظمات في تعزيز مفاهيم المواطنة الاقتصادية تبعاً لمتغير الجنس. - عدم وجود فروق ذات دلالة إحصائية بين متوسطات استجابات الشباب المستفيدين من أنشطة الجمعيات الأهلية الشبابية السورية المتصلة بدور تلك المنظمات في تعزيز مفاهيم المواطنة الاقتصادية تبعاً لمتغير الجنس. - وجود فروق ذات دلالة إحصائية بين دور المنظمات الشعبية الشبابية, ودور الجمعيات الأهلية الشبابية في تعزيز مفاهيم المواطنة الاقتصادية لدى الشباب من وجهة نظر الشباب المستفيدين من أنشطة كل منها, وهذه الفروق لصالح الشباب المستفيدين من أنشطة المنظمات الشعبية الشبابية لأن متوسطها أعلى, وهذا يعود إلى التزام المنظمات الشعبية الشبابية بمتابعة أنشطتها وتنفيذها بشكل مستمر. This research aims to know the role of public organizations and NGOs, whose work scope is youth, in enhancing the concepts of economic citizenship in young beneficiaries of these organizations' activities. These concepts are the right to work, protected consumer's and producer's rights and, saving energy sources, and maintenance of public facilities and property, etc. To achieve the research objectives a questionnaire was designed and distributed to a sample of / 187 / beneficiaries of the activities of Syrian public organizations and NGOs. The sample included 96 male beneficiaries, and female 91 beneficiaries. It was selected through the stratified random sample method, depending on the statistical sample principle. The analysis of the study yielded the following results: - There are no statistically significant differences among the average answers of young people benefiting from the activities of public organizations as to the role of these organizations in enhancing the concepts of economic citizenship regarding to the variable of gender. - There are no statistically significant differences among the average answers of young people benefiting from the activities of the Syrian youth NGOs as to the role of these organizations in enhancing the concepts of economic citizenship regarding to the variable of gender. - There are statistically significant differences between the role of public organizations of youth, and the role of Syrian youth NGOs in enhancing the concepts of economic citizenship among young people from the perspective of young beneficiaries of the activities of each of them. These differences are in favor of those benefiting from the activities of public youth organizations because its average is higher. This is due to youth's commitment to following up public organizations and the implementation of its activities on an ongoing basis.